Assessment of Apparent Diffusion Coefficient of Normal Fetal Brain Development from Gestational Age Week 24 Up to Term Age: A Preliminary Study - Han, Rui; Huang, Lu; Sun, Ziyan; Zhang, Dongyou; Chen, Xinlin; Yang, Xiaohong; Cao, Zhongqiang (Fetal diagnosis and therapy, 2015)
Objectives: This study was designed to investigate the feasibility of apparent diffusion coefficient (ADC) values in evaluating normal fetal brain development from gestational week 24 up to term age. Methods: Diffusion-weighted imaging (DWI) was performed on 40 normal fetuses (with normal results on sonography and normal fetal MRI results), with two b-values of 0 and 600 s/mm 2 in the three (x, y, z) orthogonal axes. Ten regions of interest (ROIs) were manually placed symmetrically in the bilateral frontal white matter (FWM), occipital white matter (OWM), thalamus (THAL), basal ganglia (BG), and cerebellar hemispheres (CH). ADC values of the ten ROIs in all subjects were measured by two radiologists independently. One-way ANOVA was used to calculate the differences among the five regions in the fetal brain and linear regression analysis was used to evaluate the correlation between ADC values and gestational age (GA). p < 0.05 was considered significantly different. Results: Mean GA was 31.3 ± 3.9 (range 24-41) weeks. The overall mean ADC values (×10 -6 mm 2 /s) of the fetuses were 1,800 ± 214 (FWM), 1,400 ± 100 (BG), 1,300 ± 126 (THAL), 1,700 ± 133 (OWM) and 1,400 ± 155 (CH), respectively. The ADC value of BG was not significantly different from those of THAL and CH, while the other four ROIs had significant differences with each other. The ADC values of BG, THAL, OWM and CH had strong negative correlations with increasing GA (R were -0.568, -0.716, -0.830 and -0.700, respectively, all p < 0.01), OWM declined fastest with GA, followed by CH and THAL, the slowest being BG. The ADC value of FWM had no significant change with GA (p = 0.366). Conclusions: The measurement of ADC values is feasible to evaluate fetal brain development with high reliability and reproducibility.